ANALISIS EFEKTIVITAS MESIN DIESEL WARTSILA W20V34DF BERBASIS PERFORMANCE TEST (PT) PADA PEMBANGKIT LISTRIK TENAGA MESIN GAS (PLTMG) AMBON - Ridho Aldino Saputra; Didik Aribowo (Fakultas Teknik Universitas Cenderawasih, 2022)
Gas Engine Power Plant (PLTMG) is a type of power plant that uses dual fuel, namely LNG (liquid natural gas) and BBM (fuel oil). Along with the continuous operation of the Ambon Peaker PLTMG unit. So do not rule out that the engine performance will decrease. The decrease in engine performance will affect the power supply of electrical energy to the electricity demand network. In order to maintain a reliable, safe, and efficient electricity supply. So the performance of the engine performance will always be monitored regularly. This is done so that the performance of the engine performance is always properly monitored. One of the performances to assess the performance of the Ambon Peaker PLTMG unit is by carrying out a Performance Test. The method used in industrial practice activities carried out at the Ambon Peaker 30 MW PLTMG is practical work in the form of field research.